1982
DOI: 10.1111/j.1432-1033.1982.tb06737.x
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Motion of Cytochrome c Derivatives Bound to Membranes Measured by Fluorescence and Phosphorescence Anisotropy

Abstract: Molecular motion of metal-free and metal-substituted cytochrome c derivatives was examined using the anisotropy of emissions from the singlet and the triplet states. The anisotropy of fluorescence provides a means to study the motion of cytochrome c in the nanosecond time scale, since the fluorescence lifetime of metal-free cytochrome c is around 10 ns. We find that the anisotropy of fluorescence of metal-free cytochrome c when bound to mitochondria does not decay, but when bound to phospholipids has a small c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The kinetics of electron transfer from cyt.c through the oxidase to molecular oxygen exhibit two or three phases (Thompson, Suarez & Ferguson-Miller, 1982); the polarographically determined rate of 02 reduction is much faster than the net rate of spectroscopic appearance of oxidized cyt.c (Ferguson-Miller, Brautigan & Margoliash, 1978), suggesting that the initial rapid phase is due to multiple turnovers of bound cyt.c prior to dissociation from the oxidase. Consistently, a phosphorescent cyt.c derivative rotates at the same slow rate as cytochrome oxidase bound to mitochondrial membranes (Dixit et al, 1982), suggesting complexation, and cyt.c covalently bound to either the reductase or the oxidase is still capable of mediating electron transfer (Erecinska, Davis & Wilson, 1980;Waring et al, 1980); a mechanism of rapid oscillation of cyt.c between reductase and oxidase could explain fast respiratory rates. Hackenbrock et al (1986) severely criticized the above interpretation on the basis that under physiological conditions of 150 mM ionic strength, cytochrome c is readily dissociated from the membrane and appears free to undergo three-dimensional diffusion (Gupte et al, 1984) in the intermembrane space; accordingly, duroquinol oxidase activity is enhanced by increasing ionic strength in parallel with the diffusion coefficient of cyt.c.…”
Section: The Puzzle Of Cytochrome C Mobilitymentioning
confidence: 79%
See 1 more Smart Citation
“…The kinetics of electron transfer from cyt.c through the oxidase to molecular oxygen exhibit two or three phases (Thompson, Suarez & Ferguson-Miller, 1982); the polarographically determined rate of 02 reduction is much faster than the net rate of spectroscopic appearance of oxidized cyt.c (Ferguson-Miller, Brautigan & Margoliash, 1978), suggesting that the initial rapid phase is due to multiple turnovers of bound cyt.c prior to dissociation from the oxidase. Consistently, a phosphorescent cyt.c derivative rotates at the same slow rate as cytochrome oxidase bound to mitochondrial membranes (Dixit et al, 1982), suggesting complexation, and cyt.c covalently bound to either the reductase or the oxidase is still capable of mediating electron transfer (Erecinska, Davis & Wilson, 1980;Waring et al, 1980); a mechanism of rapid oscillation of cyt.c between reductase and oxidase could explain fast respiratory rates. Hackenbrock et al (1986) severely criticized the above interpretation on the basis that under physiological conditions of 150 mM ionic strength, cytochrome c is readily dissociated from the membrane and appears free to undergo three-dimensional diffusion (Gupte et al, 1984) in the intermembrane space; accordingly, duroquinol oxidase activity is enhanced by increasing ionic strength in parallel with the diffusion coefficient of cyt.c.…”
Section: The Puzzle Of Cytochrome C Mobilitymentioning
confidence: 79%
“…No immobile fraction of cyt.c was found at high ionic strength by Gupte et al (1984), whereas Vanderkooi et al (1985 found that a fraction of 3 nmol of cyt.c derivative per mg protein remained immobile and tightly bound to the membrane. Dixit et al (1982) found that a phosphorescent cyt.c derivative rotates at the same slow rate as cytochrome oxidase bound to mitochondrial membranes, suggesting complexation between the two molecules; the smaller radius of cyt.c, in fact, would make its rotation much faster if the molecule were completely free.…”
Section: Diffusion Of Ubiquinonementioning
confidence: 99%
“…Consistent with this idea is the finding that only about half of the cytochrome c oxidase appears to be rotationally mobile (17,18). The rotational mobility of zinc cytochrome c also showed biphasicity which was interpreted to be due to rotation in a cone, but could also be due to an immobilized fraction (6). Some mobility of the electron-transfer components is, however, suggested by observations indicating the independent diffusion of cytochrome oxidase and cytochrome bcl complex (13) and their electrophoretic mobility (25) as well as by electron micrographs of inner mitochondrial membranes labeled with antibodies against oxidase and reductase which show random distribution (12).…”
Section: Discussionmentioning
confidence: 95%
“…As an alternative explanation for the results of Hochman et al (1982), it may be that there is some constraint to long-range lateral diffusion (as measured by fluorescence recovery after photobleaching) and that only short-range motions are necessary in the mitochondrial membrane (Cherry, 1979;Kawato et al, 1981). Dixit et al (1982) measured the rotational diffusion of zinc cytochrome c on mitochondrial membranes by using the decay of phosphorescence anisotropy. The rotational relaxation time was similar to that measured for cytochrome oxidase (Kawato et al, 1981), suggesting that cytochrome c is associated with its oxidase in situ.…”
Section: Discussionmentioning
confidence: 99%